The Guidance of Head-Neck-Aorta CT Angiography in Acute Type A Aortic Dissection Patients - Zhao, Hongliang; Li, Chengxiang; Xu, Jian; Xue, Chao; Chang, Yingjuan; Wei, Mengqi; Shang, Lei; Lin, Shushen; Duan, Weixun; Zheng, Minwen (JACC. Asia, 2025)
The benefit of preoperative craniocervical artery imaging has not been elucidated for decision-making during the surgical repair of acute type A aortic dissection (ATAAD). The purpose of this study was to explore the clinical implication of a preoperative extended head-neck-aorta computed tomography angiography (CTA) among ATAAD patients. ATAAD patients undergoing surgical repair were retrospectively enrolled. Preoperatively, 215 patients underwent aortic CTA (conventional group) and 220 underwent extended CTA (extended group). In the extended group, the surgical team was informed of assessment of craniocervical arteries before the operation. The primary endpoint was postoperative transient neurological deficit and permanent neurological deficit. A 1:1 propensity score matching analysis was performed to account for baseline differences between groups, resulting in 154 pairs. In the extended group, 135 patients were free of preoperative neurological symptoms, but 35 (25.9%) presented with severely stenosed or occluded common carotid artery. Common carotid artery reconstruction and cannulation combined with femoral artery cannulation (24.1% vs 5.1%; P < 0.001) and bilateral antegrade selective cerebral perfusion during hypothermic circulatory arrest (56.4% vs 19.1%; P < 0.001) were more adopted in the extended group. In the matched cohort, the extended CTA was significantly associated with fewer postoperative permanent neurological deficit (adjusted OR: 0.186; 95% CI: 0.059-0.587; P = 0.004) after adjustment with logistic regression. The extended head-neck-aorta CTA protocol provided additional anatomical clarity preoperatively for modified surgical strategies and may subsequently improved the neurological outcomes of ATAAD. [Display omitted]